Cigarette smoke extract stimulates PCSK9 production in HepG2 cells via ROS/NF-[kappa]B signaling - Ma, Baitao; Wang, Xuebin; Zhang, Rui; Niu, Shuai; Rong, Zhihua; Ni, Leng; Di, Xiao; Han, Qin; Liu, Changwei (Molecular medicine reports, 2021)
Cigarette smoke (CS) exposure is a risk factor for dyslipidemia and atherosclerosis. Reduced expression of low-density lipoprotein receptor (LDLR) in hepatocytes may be one of the underlying mechanisms for these disorders. The aim of the present study was to investigate the molecular mechanism underlying the regulatory effect of CS extract (CSE) on proprotein convertase subtilisin/kexin type 9 (PCSK9) and low LDLR expression in HepG2 cells. PCSK9 and LDLR mRNA and protein expression levels in HepG2 cells were evaluated after CSE treatment via reverse transcription-quantitative polymerase chain reaction and western blotting, respectively. In addition, total intracellular reactive oxygen species (ROS) production was determined via 2,7-dichlorofluorescein diacetate fluorescence. CSE significantly increased PCSK9 expression and inhibited LDLR expression in a time- and concentration-dependent manner. Furthermore, CSE significantly induced ROS production and nuclear factor [kappa]B (NF-[kappa]B) activation. However, pretreatment with a ROS scavenger or an NF-[kappa]B inhibitor significantly attenuated the CSE-induced changes in PCSK9 and LDLR expression. In addition, pretreatment with melatonin markedly reduced ROS production, NF-[kappa]B activation and PCSK9 expression, and increased LDLR expression in the CSE-treated cells. These data suggest that melatonin inhibits CSE-regulated PCSK9 and LDLR production in HepG2 cells via ROS/NF-[kappa]B signaling. Key words: cigarette smoke extract, reactive oxygen species, NF-[kappa]B, proprotein convertase subtilisin/kexin type 9, low-density lipoprotein receptor, atherosclerosis